If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(0 + -1)(0 + -2) = 0 Combine like terms: 0 + -1 = -1 3x(-1)(0 + -2) = 0 Combine like terms: 0 + -2 = -2 3x * -1(-2) = 0 Reorder the terms for easier multiplication: 3 * -1 * -2x = 0 Multiply 3 * -1 -3 * -2x = 0 Multiply -3 * -2 6x = 0 Solving 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 0 Simplifying x = 0
| 9x-54=27+12x | | 12+11=124 | | 2(x-8)+4=-6+8x | | 3/8+0.5= | | -x^3-10x^2-32x-29=0 | | 1/x=.0094 | | 28x=-8(7-3x) | | -14+7x=4x+34 | | 1.54x=3.85 | | 3.85x=1.54 | | -x^5+3x^3-3x=0 | | 4a-8=9a-48 | | 10P=7E | | 32-x=-29 | | 8x-20=8+6x | | 3x-14=6+7 | | 120x^3-144x^2+15x-18=0 | | 120x^3-144x^2+15x-84=0 | | 3q-98=2q | | 3v-1=6v-49 | | 5x^4+6x^3+x^2=0 | | 243-3x^2-3y^2=0 | | D/6=(-7) | | 10t-29=7t-17 | | 10+9=3x+34 | | 3x-1/48 | | x+(x+1)=x-1 | | y3/2-1 | | 8x-9=2+5x | | 7x-9=21+5x | | 12e-(19)=7-e | | (9x-3)=(3x+6) |